2007
DOI: 10.1002/ppul.20593
|View full text |Cite
|
Sign up to set email alerts
|

Cutoff value of lipid‐laden alveolar macrophages for diagnosing aspiration in infants and children

Abstract: Chronic passage of gastric and/or alimentary material into the airways is a frequent and difficult-to-diagnose condition. Because alveolar macrophages phagocytose aspirated material, it has been suggested that their identification is a useful diagnostic method. To know the usefulness of the lipid-laden alveolar macrophages (LLAM) index as a diagnostic tool for aspiration, children from 1 month to 16 years of age were included in three groups: G-I, children with pulmonary pathology and suspicion of aspiration b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 21 publications
2
35
0
1
Order By: Relevance
“…(31) The investigation of lipid-laden alveolar macrophages (LLAM) is classically cited as an aid in the diagnosis of aspiration associated with diseases that originate in the gastrointestinal tract, such as the gastroesophageal reflux disease (GERD). (32,33) It is considered that, when there is clinical suspicion, a LLAM index higher than 165 is useful for the diagnosis of aspiration, with sensitivity of 98.6% and specificity of 78.0%. (32) However, this index has been greatly questioned because of its low specificity and because of the large variability in the cut-off values cited in different studies.…”
Section: Cystic Fibrosismentioning
confidence: 99%
See 2 more Smart Citations
“…(31) The investigation of lipid-laden alveolar macrophages (LLAM) is classically cited as an aid in the diagnosis of aspiration associated with diseases that originate in the gastrointestinal tract, such as the gastroesophageal reflux disease (GERD). (32,33) It is considered that, when there is clinical suspicion, a LLAM index higher than 165 is useful for the diagnosis of aspiration, with sensitivity of 98.6% and specificity of 78.0%. (32) However, this index has been greatly questioned because of its low specificity and because of the large variability in the cut-off values cited in different studies.…”
Section: Cystic Fibrosismentioning
confidence: 99%
“…(32,33) It is considered that, when there is clinical suspicion, a LLAM index higher than 165 is useful for the diagnosis of aspiration, with sensitivity of 98.6% and specificity of 78.0%. (32) However, this index has been greatly questioned because of its low specificity and because of the large variability in the cut-off values cited in different studies. (32) One group of authors (34) reported that more sensitive tests, such as pH-metry, should remain as the gold standard for the diagnosis of GERD and proposed that the identification of lipid-laden macrophages should be reserved for children with no definitive diagnosis and no improvement with the proposed therapy.…”
Section: Cystic Fibrosismentioning
confidence: 99%
See 1 more Smart Citation
“…BAL may be useful for documenting the presence of blood or hemosiderin-laden macrophages in the lower respiratory tract (78), although this does not provide a specific explanatory diagnosis (103). The accuracy of BAL for the diagnosis of gastroesophageal reflux is the subject of debate, and several studies suggest that it is neither sensitive nor specific (97,98). Investigators have used BAL histologic studies to confirm abnormal cell markers in patients previously diagnosed with Langerhans histiocytosis (82,84), and inflammatory cytokine levels have been investigated in BAL fluid from patients previously diagnosed with sarcoidosis (85).…”
Section: Diagnostic Testsmentioning
confidence: 99%
“…Findings consistent with pulmonary alveolar proteinosis should lead to an investigation of surfactant dysfunction mutations, GM-CSF pathway abnormalities, and lysinuric protein intolerance (80,(88)(89)(90)(91)(92)(93)(94)(95). Evidence of aspiration may be obtained by lipid staining of alveolar macrophages (96), although the sensitivity and specificity of the finding is questionable (97,98). Measuring gastric pepsin levels (99) and/or determining alveolar macrophage localization of milk proteins (100, 101) are more recently developed techniques, which are still undergoing study.…”
Section: Diagnostic Testsmentioning
confidence: 99%